THE INVESTIGATION OF THE MEDICINAL POTENTIAL OF ALCEA KURDICA ALEF. IN NATURE AND TISSUE CULTURE - Gormez, Gul; Battal, Abdulhamit; Dalar, Abdullah; Turker, Musa (SOC STIINTE FARMACEUTICE ROMANIA, 2022)
Alcea kurdica Alef. (AK) a hollyhock has been used in folk medicine to treat various diseases. Though its extensive utilization in traditional medicine, experimental studies regarding to its phytochemical composition is limited. The aim of this study was to determine the antioxidant capacity and phenolic composition of ethanol extract of AK plant collected from the natural environment in different vegetation periods (June-flowering, July-fruiting, August-seeding) and to control its antioxidant capacity and phenolic composition by in vitro shoot tip culture. AK plant at the flowering period had the highest antioxidant capacity, while the lowest activity was determined at the seeding period according to results. Phenolic acids dominated by gallic, chlorogenic and caffeic acids were determined as the major phenolics. According to in vitro results, the use of 1-naphthylacetic acid (NAA) and 6-benzylaminopurine (BA) alone caused significant decrease in the three phenolic acids content compared to the control. On the other hand, combination of NAA and BA caused significant increase in phenolic acids content compared to the control. Moreover, significant increase in ORAC was observed in AK extract obtained from in vitro Murashige & Skoog (MS) media culture supplemented with NAA and BA combination. 15 min of UV exposure negatively affected the antioxidant capacity and phenolic content.
Keywords: Alcea kurdica; antioxidant capacity; phenolic acids; medicinal plant; IN-VITRO; ANTIOXIDANT PROPERTIES; CHLOROGENIC ACID; PHENOLIC CONTENT; PLANT-EXTRACTS; BIOSYNTHESIS; OFFICINALIS; METABOLISM; STRESS; Pharmacology & Pharmacy